Analisa Strategi Pengembangan Pada Lembaga Verifikasi Industri (Studi Kasus: PT. XY) - Azhari, Wisnu; Ferianto, Ferianto (Jurnal Teknik Industri Terintegrasi (JUTIN), 2025)
PT XY is a National Independent Assurance company with four business sectors, one of which comprises the Government Mandatory Scheme business sub-unit responsible for conducting industrial verification activities. The purpose of this research is to develop business strategies through an analysis of the company's environment, both internally and externally, to determine the company's position as the foundation for formulating business strategies. By using the SWOT matrices and the Quantitative Strategic Planning Matrix (QSPM), the company will gain an understanding of its strengths, weaknesses, opportunities, and threats. The alternative strategies obtained were 8 alternative strategies. The recommended priority development strategy is to establish a marketing team to increase the number of customers for industrial verification.